Composite phase layered oxide positive electrode material and preparation method and application thereof
Synthesizing composite phase layered oxide positive electrode material by solid phase reaction method solves the problems of cumbersome preparation steps and low yield in the prior art, and realizes an efficient and low-cost preparation method. The material exhibits high capacity, long cycle life and excellent rate performance.
Patent Information
- Application Number
- CN202510235259.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-05-30
AI Technical Summary
The preparation method of the existing potassium ion battery composite phase layered oxide positive electrode material is complicated, the output is low, the cost is high, and it is difficult to achieve large-scale industrial production.
The composite phase layered oxide positive electrode material was synthesized by ball milling and calcining using solid phase reaction method, and the content of K elements during sintering was adjusted, which promoted the transformation of the material from P3 to P2 phase and the transformation of polycrystals to single crystals, and accurately regulated the phase ratio and grain size.
It realizes an efficient and simple preparation method, suitable for large-scale industrial production, and the material has high capacity, long cycle life and excellent rate performance.
Smart Images

Figure CN120072920A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of potassium ion batteries, and relates to a composite phase layered oxide cathode material, a preparation method thereof, and an application thereof. Background Art
[0002] Secondary battery energy storage devices represented by lithium ion batteries have become the fastest growing energy storage technology globally due to advantages such as high energy density, long cycle life, high safety, and environmental friendliness. However, nowadays, lithium ion batteries are facing the severe situation of short lithium resources, difficult mining, and excessively high battery manufacturing costs, which seriously restricts their further development in the field of large-scale energy storage. Developing a new type of secondary ion battery energy storage technology with low cost, high efficiency, high safety, and high specific energy is extremely urgent. Potassium ion batteries have rich potassium resources and low costs, have the same working principle as lithium ion batteries, and have similar hydrogen standard electrode potentials. In addition, potassium can alloy with graphite anodes, and aluminum can be used as a current collector. Therefore, from the perspective of further reducing production costs, reducing battery mass, and increasing energy density, potassium ion batteries have broad application prospects in the future large-scale energy storage field. As the core component of potassium ion batteries, the cost and performance of the cathode material directly determine the overall cost and key performance parameters such as battery energy density and cycle life. Due to its high theoretical capacity and simple synthesis method, layered oxides have always been considered strong competitors among potassium ion battery cathode materials.
[0003] Currently, the most widely studied layered oxides are of the P-type structure, which are divided into P3 and P2-type structures according to the data of the transition metal layer in the unit cell. Generally speaking, the AM layer spacing of the P3-type structure is larger, so it often has better diffusion kinetics, but it also causes the P3-type structure to be more likely to absorb water molecules in the air and undergo K + and H + exchange, which damages the battery performance. Therefore, constructing a P3 / P2 composite structure and integrating the advantages of multiple phase structures can provide a possible strategy for stabilizing the phase structure and improving the electrochemical performance of the material. In addition, during the solid-phase reaction process, the grain size will have a significant impact on the material performance. Polycrystalline materials have better kinetic performance due to the short potassium ion diffusion path; while single crystals can resist crystal cracking problems caused by long-term cycling of the battery and achieve better cycling performance. In the prior art, the method for constructing the composite phase of potassium ion batteries still uses the electrochemical ion exchange method. For example, the preparation method disclosed in Invention CN118367099A synthesizes a sodium ion battery composite phase layered oxide first, assembles the battery, and obtains a P3 / P2 composite phase material through sodium / potassium ion exchange during the electrochemical process; however, such methods have cumbersome steps, low yield, and high costs, and it is difficult to achieve commercialization.
[0004] Therefore, there is a need for a method or device with high yield, low cost, and simple steps that can be mass-produced industrially to solve the above technical problems. Summary of the Invention
[0005] The technical solution adopted by the present invention to solve the technical problems is as follows: A composite-phase layered oxide cathode material, with the chemical formula: K x Mn a Li b Mg c Ti d Ni e O 2 , where 0.3 ≤ x ≤ 0.8, 0.2 ≤ a ≤ 0.96, 0 < b ≤ 0.2, 0 < c ≤ 0.2, 0 < d ≤ 0.2, 0 < e ≤ 0.2; the cathode material is a composite-phase layered cathode material for potassium-ion batteries synthesized by a solid-state reaction method.
[0006] Preferably, the K source of the cathode material includes at least one of potassium carbonate, potassium hydroxide, and potassium bicarbonate; the Li source of the cathode material includes at least one of lithium carbonate and lithium hydroxide; the Mg source of the cathode material includes at least one of magnesium carbonate and magnesium hydroxide; the Ti source of the cathode material includes at least one of titanium monoxide and titanium dioxide; the Ni source of the cathode material includes at least one of nickel oxide, nickel carbonate, and nickel hydroxide; the Mn source of the cathode material includes at least one of manganese dioxide, manganese tetroxide, manganese(III) oxide, and manganese monoxide.
[0007] Preferably, in the chemical formula K x Mn a Li b Mg c Ti d Ni e O 2 , a = 0.77, b = 0.03, c = 0.03, d = 0.07, e = 0.1.
[0008] More preferably, in the chemical formula K x Mn a Li b Mg c Ti d Ni e O 2 , x = 0.35, 0.4, 0.5, 0.55, 0.6, 0.65.
[0009] The present invention also discloses a preparation method of a composite-phase layered oxide cathode material, which is used to prepare the above-mentioned composite-phase layered oxide cathode material, and the preparation method includes the following steps:
[0010] Step S1: Ball-mill a mixture of a K source, a Li source, a Mg source, a Ti source, a Ni source, and a Mn source in proportion to obtain a mixed material.
[0011] Step S2: Calcinate the mixed material prepared in Step S1 to obtain a layered oxide cathode material.
[0012] Preferably, in Step S1, the rotation speed of the ball-milling is 200 - 600 r / min, and the ball-milling time is 2 - 10 h.
[0013] More preferably, in Step S1, the rotation speed of the ball-milling is 300 - 400 r / min, and the ball-milling time is 6 - 9 h.
[0014] Preferably, in Step S2, the calcination is carried out in an air or oxygen atmosphere, sintered at 800 - 1200 °C for 10 - 30 h; the heating rate of the calcination is 1 - 10 °C / min, and the cooling rate is 1 - 10 °C / min; after the calcination is completed, it is taken out under the condition of 20 - 300 °C and stored in an anhydrous and anaerobic environment.
[0015] More preferably, in Step S2, the calcination is carried out at 850 - 950 °C for 15 - 24 h; the heating rate of the calcination is 3 - 5 °C / min, and the cooling rate is 3 - 5 °C / min; after the calcination is completed, it is taken out under the condition of 150 - 300 °C and stored in an anhydrous and anaerobic environment.
[0016] The present invention also discloses an application of a composite-phase layered oxide cathode material. The application uses the above-mentioned composite-phase layered oxide cathode material, and this application is to prepare a potassium-ion battery. The potassium-ion battery includes: an active material, conductive carbon black, and PVDF, and the active material is prepared using the composite-phase layered oxide cathode material.
[0017] Preferably, the mass ratio of the active material, conductive carbon black, and PVDF is 7 - 9:2 - 0.5:1 - 0.5.
[0018] The beneficial effects of the present invention are:
[0019] 1. By using the solid-phase reaction method, the present invention can calcinate the oxide cathode material in two steps. Therefore, the preparation method of the present invention is simple, efficient, and has a high yield, and can be applied to large-scale industrial production.
[0020] 2. By changing the content of K element during the sintering process, the present invention promotes the gradual transformation of the layered material from the P3 phase to the P2 phase and the gradual transformation from polycrystalline to single crystal, precisely regulates the P3 / P2 composite phase structure with different grain sizes and different phase ratios, so as to realize the composite phase transition metal layered oxide material with high capacity and long cycle life. When the composite phase layered oxide cathode material of the present invention is applied to the cathode of a potassium ion battery, the battery has a high specific capacity and cycle stability. The composite phase structure has a specific capacity of 100-110 mAh / g at 1.5-4.0 V in the potassium ion battery, and has excellent cycle performance. When cycling 100 times at a current density of 1C (1C = 100 mA / g), the capacity retention rate exceeds 80%. Description of the Drawings
[0021] Figure 1 is the XRD pattern of the cathode materials prepared in Examples 2-5 of a composite phase layered oxide cathode material, its preparation method and application of the present invention;
[0022] Figure 2 is the SEM image of the cathode materials prepared in Examples 2-5 of the present invention;
[0023] Figure 3 is the first charge-discharge curve of the cathode materials prepared in Examples 2-5 of the present invention at 0.1C;
[0024] Figure 4 is the cycle performance graph of the cathode materials prepared in Examples 2-5 of the present invention at 1C;
[0025] Figure 5 is the rate performance graph of the cathode materials prepared in Examples 2-5 of the present invention. Detailed Embodiments
[0026] Next, the relevant technologies in the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work belong to the scope of protection of the present invention.
[0027] Refer to Figures 1 to 5 As shown, the composite phase layered oxide cathode material of this embodiment has the chemical formula: K x Mn a Li b Mg c Ti d Ni e O 2, 0.3 ≤ x ≤ 0.8, 0.2 ≤ a ≤ 0.96, 0 < b ≤ 0.2, 0 < c ≤ 0.2, 0 < d ≤ 0.2, 0 < e ≤ 0.2; The cathode material is a composite phase layered cathode material for potassium ion batteries synthesized by a solid-state reaction method.
[0028] Further, the K source includes at least one of potassium carbonate, potassium hydroxide, and potassium bicarbonate; the Li source includes at least one of lithium carbonate and lithium hydroxide; the Mg source includes at least one of magnesium carbonate and magnesium hydroxide; the Ti source includes at least one of titanium monoxide and titanium dioxide; the Ni source includes at least one of nickel oxide, nickel carbonate, and nickel hydroxide; the Mn source includes at least one of manganese dioxide, manganese tetroxide, manganese sesquioxide, and manganese monoxide.
[0029] Further, in the chemical formula K x Mn a Li b Mg c Ti d Ni e O 2 , a = 0.77, b = 0.03, c = 0.03, d = 0.07, e = 0.1.
[0030] Even further, in the chemical formula K x Mn a Li b Mg c Ti d Ni e O 2 , x = 0.35, 0.4, 0.5, 0.55, 0.6, 0.65; Adjust the content of the K source during the synthesis process to make the synthesized layered structure show a gradual transition process from the P3 phase, the P3 / P2 composite phase to the P2 phase, and a gradual transition from polycrystalline to single crystal, where the K 0.55 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 material has relatively excellent cycle stability.
[0031] This embodiment also discloses a preparation method of a composite phase layered oxide cathode material, including the following steps:
[0032] Step S1: Ball-mill a mixture of a K source, an Li source, an Mg source, a Ti source, a Ni source, and an Mn source in proportion to obtain a mixed material;
[0033] Step S2: Calcinate the mixed material prepared in Step S1 to obtain a composite phase layered oxide cathode material.
[0034] When the composite-phase layered oxide cathode material obtained by this method is used as the cathode material of a potassium-ion battery, it has good stability and rate performance. This method is simple to operate, easy to prepare, green and environmentally friendly, and can be applied to the production process of large-scale products.
[0035] Furthermore, in the step S1, the rotation speed of the ball milling is 200 - 600 r / min, and the ball milling time is 2 - 10 h.
[0036] Even further, in the step S1, the rotation speed of the ball milling is 300 - 400 r / min, and the ball milling time is 6 - 9 h.
[0037] Furthermore, in the step S2, the calcination is carried out in an air or oxygen atmosphere, sintered at 800 - 1200 °C for 10 - 30 h; the heating rate of the calcination is 1 - 10 °C / min, and the cooling rate is 1 - 10 °C / min; after the calcination is completed, it is taken out under the condition of 20 - 300 °C and stored in an anhydrous and anoxic environment.
[0038] Even further, in the step S2, the calcination is sintered at 850 - 950 °C for 15 - 24 h; the heating rate of the calcination is 3 - 5 °C / min, and the cooling rate is 3 - 5 °C / min; after the calcination is completed, it is taken out under the condition of 150 - 300 °C and stored in a glove box.
[0039] The present invention also discloses an application of a composite-phase layered oxide cathode material. The application uses the above-mentioned composite-phase layered oxide cathode material, and this application is to prepare a potassium-ion battery. The potassium-ion battery includes: an active material, conductive carbon black, and PVDF, and the active material uses the composite-phase layered oxide cathode material.
[0040] Furthermore, the mass ratio of the active material, conductive carbon black, and PVDF is 7:2:1 - 9:0.5:0.5.
[0041] Examples
[0042] Example 1
[0043] A preparation method of a composite-phase layered oxide cathode material, comprising the following steps:
[0044] S1. According to the molar ratio of K:Li:Mg:Ti:Ni:Mn = 0.35:0.03:0.03:0.07:0.1:0.77, K 2 CO 3 , Li 2 CO 3 , MgO, TiO 2 , NiO, Mn 2 O3 Put them into a ball mill in sequence, and ball-mill and mix them at a speed of 400 r / min for 6 h. The ball-milling medium is zirconia balls to obtain a mixed material;
[0045] S2. Press the mixed material obtained in step S1 at 18 MPa, transfer it to a muffle furnace, heat it to 900 °C at a heating rate of 5 °C / min, sinter it in an air atmosphere for 24 h, then cool it at a cooling rate of 5 °C / min to 300 °C and transfer it to a glove box for storage to obtain the layered cathode material K 0.35 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 ;
[0046] Example 2
[0047] A preparation method of a composite-phase layered oxide cathode material, comprising the following steps:
[0048] S1. According to the molar ratio of K:Li:Mg:Ti:Ni:Mn = 0.4:0.03:0.03:0.07:0.1:0.77, put K 2 CO 3 、Li 2 CO 3 、MgO, TiO 2 、NiO, Mn 2 O 3 Put them into a ball mill in sequence, and ball-mill and mix them at a speed of 400 r / min for 6 h. The ball-milling medium is zirconia balls to obtain a mixed material;
[0049] S2. Press the mixed material obtained in step S1 at 18 MPa, transfer it to a muffle furnace, heat it to 900 °C at a heating rate of 5 °C / min, sinter it in an air atmosphere for 24 h, then cool it at a cooling rate of 5 °C / min to 300 °C and transfer it to a glove box for storage to obtain the layered cathode material K 0.4 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 ;
[0050] Example 3
[0051] A preparation method of a composite-phase layered oxide cathode material, comprising the following steps:
[0052] S1. According to the molar ratio of K:Li:Mg:Ti:Ni:Mn = 0.5:0.03:0.03:0.07:0.1:0.77, put K2 CO 3 , Li 2 CO 3 ,MgO,TiO 2 、NiO、Mn 2 O 3 Put them into a ball mill in turn, and mix them by ball milling at a speed of 400 r / min for 6 h, with zirconium oxide balls as the ball milling medium, to obtain a mixture;
[0053] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 900°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a composite layered positive electrode material K 0.5 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 ;
[0054] Example 4
[0055] The method for preparing a composite layered oxide positive electrode material comprises the following steps:
[0056] S1. K: Li: Mg: Ti: Ni: Mn = 0.55: 0.03: 0.03: 0.07: 0.1: 0.77 2 CO 3 , Li 2 CO 3 ,MgO,TiO 2 、NiO、Mn 2 O 3 Put them into a ball mill in turn, and mix them by ball milling at a speed of 400 r / min for 6 h, with zirconium oxide balls as the ball milling medium, to obtain a mixture;
[0057] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 900°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a composite layered positive electrode material K 0.55 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 ;
[0058] Example 5
[0059] Preparation method of composite phase layered oxide cathode material, comprising the following steps:
[0060] S1. According to the molar ratio of K:Li:Mg:Ti:Ni:Mn = 0.6:0.03:0.03:0.07:0.1:0.77, put K 2 CO 3 , Li 2 CO 3 , MgO, TiO 2 , NiO, Mn 2 O 3 into a ball mill in sequence, ball mill and mix at a rotation speed of 400 r / min for 6 h, with zirconia balls as the ball milling medium, to obtain a mixed material;
[0061] S2. Press the mixed material obtained in step S1 into tablets under 18 MPa, transfer it to a muffle furnace, heat it up to 900 °C at a heating rate of 5 °C / min, sinter it for 24 h in an air atmosphere, then cool it at a cooling rate of 5 °C / min to 300 °C and transfer it to a glove box for storage, to obtain the layered cathode material K 0.6 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 ;
[0062] Example 6
[0063] Preparation method of composite phase layered oxide cathode material, comprising the following steps:
[0064] S1. According to the molar ratio of K:Li:Mg:Ti:Ni:Mn = 0.65:0.03:0.03:0.07:0.1:0.77, put K 2 CO 3 , Li 2 CO 3 , MgO, TiO 2 , NiO, Mn 2 O 3 into a ball mill in sequence, ball mill and mix at a rotation speed of 400 r / min for 6 h, with zirconia balls as the ball milling medium, to obtain a mixed material;
[0065] S2. Press the mixed material obtained in step S1 into tablets under 18 MPa, transfer it to a muffle furnace, heat it up to 900 °C at a heating rate of 5 °C / min, sinter it for 24 h in an air atmosphere, then cool it at a cooling rate of 5 °C / min to 300 °C and transfer it to a glove box for storage, to obtain the layered cathode material K 0.65 Li 0.03 Mg 0.03 Ti 0.07Ni 0.1 Mn 0.77 O 2 ;
[0066] Application and Performance Testing
[0067] The layered oxide cathode materials prepared in the above examples and comparative examples were respectively used to construct potassium-ion coin cells, and the specific operations are as follows:
[0068] Positive electrode sheet: Grind the cathode material, conductive carbon black, and PVDF binder evenly according to a mass ratio of 7:2:1, then add an appropriate amount of NMP to make a slurry, coat it on aluminum foil, dry it in a blast drying oven at 80 °C for 1 h, and then dry it in a vacuum drying oven at 80 °C for 12 h, and cut it into a 10-mm circular positive electrode sheet;
[0069] Negative electrode sheet: A potassium metal sheet with a diameter of 12 mm;
[0070] Separator: Whatman GF / D glass fiber with a diameter of 16 mm;
[0071] Electrolyte: The electrolyte is 0.8 M KPF6 in EC:DEC (1:1)
[0072] Assemble the above positive electrode sheet, separator, negative electrode sheet, and electrolyte in a glove box filled with high-purity argon to obtain a CR2032 coin cell.
[0073] Perform the following electrochemical performance tests on the CR2032 coin cells constructed from different layered oxide cathode materials for potassium-ion batteries:
[0074] Initial discharge capacity and cycle performance test: In a thermostat, set the temperature to 25 °C and the standing time to 8 h. Table 1 is the electrochemical test table of the layered oxide cathode materials in Examples 1-6.
[0075] Table 1
[0076]
[0077] Figure 1 (a) The results show that K 0.4 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 The material is a pure P3 structure.
[0078] Figure 1 (b) The results show that K 0.5 Li 0.03 Mg 0.03 Ti 0.07 Ni0.1 Mn 0.77 O 2 The material has a P3 / P2 composite structure.
[0079] Figure 1 (c) The results show that K 0.55 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 The material has a P3 / P2 composite structure.
[0080] Figure 1 (d) The results show that K 0.6 Li 0.03 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 The material has a pure P2 structure.
[0081] Figure 1 The results show that as the K content increases, the material shows a gradual transformation process of P3 phase, P3 / P2 composite phase, and P2 phase
[0082] Figure 2 The results show that as the K content increases, the grain size of the material gradually becomes larger, and it gradually transforms from polycrystalline to single crystal.
[0083] Figure 3 The results show that as the K content gradually increases, the initial discharge capacity of the material gradually decreases.
[0084] Figure 4 The results show that as the K content gradually increases, the cycling performance first increases and then decreases, among which K 0.55 Li 0.0 3 Mg 0.03 Ti 0.07 Ni 0.1 Mn 0.77 O 2 The material has the most excellent cycling stability.
[0085] Figure 5 The results show that as the K content gradually increases, the rate performance gradually decreases.
[0086] In summary, by changing the content of K element in the solid-phase reaction, the phase ratio and grain size of the material can be precisely controlled. When the manganese-based layered oxide cathode material of the present invention is applied to the cathode of a potassium-ion battery, the battery has a high specific capacity, good cycle stability, and excellent rate performance. Therefore, the present invention has broad application prospects in the field of potassium-ion battery technology.
[0087] It should be emphasized that the above are only the preferred embodiments of the present invention, and there is no limitation to the present invention in any form. Any simple modification, equivalent change, and modification made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A composite layered oxide positive electrode material, characterized in that: The chemical formula of the positive electrode material is: K x Mn a Li b Mg c Ti d Ni e O2, where 0.3 ≤ x ≤ 0.8, 0.2 ≤ a ≤ 0.96, 0 < b ≤ 0.2, 0 < c ≤ 0.2, 0 < d ≤ 0.2, 0 < e ≤ 0.2; the positive electrode material is a composite phase layered positive electrode material for a potassium ion battery synthesized by a solid-phase reaction method.
2. A composite layered oxide positive electrode material according to claim 1, characterized in that: The K source of the positive electrode material includes: at least one of potassium carbonate, potassium hydroxide, and potassium bicarbonate; the Li source of the positive electrode material includes: at least one of lithium carbonate and lithium hydroxide; the Mg source of the positive electrode material includes: at least one of magnesium carbonate and magnesium hydroxide; the Ti source of the positive electrode material includes: at least one of titanium monoxide and titanium dioxide; the Ni source of the positive electrode material includes: at least one of nickel oxide, nickel carbonate, and nickel hydroxide; the Mn source of the positive electrode material includes: at least one of manganese dioxide, manganese tetraoxide, manganese trioxide, and manganese monoxide.
3. The composite layered oxide positive electrode material according to claim 1, characterized in that: The chemical formula K x Mn a Li b Mg c Ti d Ni e In O2, a=0.77, b=0.03, c=0.03, d=0.07, e=0.
1.
4. A composite layered oxide positive electrode material according to claim 3, characterized in that: The chemical formula K x Mn a Li b Mg c Ti d Ni e In O2, x=0.35, 0.4, 0.5, 0.55, 0.6, 0.
65.
5. A method for preparing a composite layered oxide positive electrode material, characterized in that: The preparation method is used to prepare the composite layered oxide positive electrode material according to any one of claims 1 to 4, and the preparation method comprises the following steps: Step S1: ball-milling a mixture of a K source, a Li source, a Mg source, a Ti source, a Ni source and a Mn source in proportion to obtain a mixed material; Step S2: calcining the mixture prepared in step S1 to obtain a layered oxide positive electrode material.
6. The method for preparing a composite layered oxide positive electrode material according to claim 5, characterized in that: In the step S1, the rotation speed of the ball mill is 200 to 600 r / min, and the time of the ball mill is 2 to 10 hours.
7. The method for preparing a composite layered oxide positive electrode material according to claim 6, characterized in that: In the step S1, the rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 6-9 h.
8. The method for preparing a composite layered oxide positive electrode material according to claim 5, characterized in that: In the step S2, the calcination is carried out in air or oxygen atmosphere, and the calcination is carried out at 800-1200°C for 10-30h; the heating rate of the calcination is 1-10°C / min, and the cooling rate is 1-10°C / min; after the calcination is completed, it is taken out at 20-300°C and stored in a water-free and oxygen-free environment.
9. An application of a composite layered oxide positive electrode material, characterized in that: The application adopts the composite layered oxide positive electrode material described in any one of claims 1 to 4, and the application is to prepare a potassium ion battery. The potassium ion battery comprises: an active substance, conductive carbon black and PVDF, and the active substance is prepared using the composite layered oxide positive electrode material.
10. The use of a composite layered oxide positive electrode material according to claim 9, characterized in that: The mass ratio of the active material, conductive carbon black and PVDF is 7-9:2-0.5:1-0.5.